1997
DOI: 10.1002/eji.1830270229
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of Lck and Fyn protein tyrosine kinases to intraepithelial lymphocyte development

Abstract: The developmental stages and the role of protein tyrosine kinases (PTK) in the maturation of CD3+CD8 alpha alpha+ intraepithelial lymphocytes (IEL) have not been extensively characterized. However, comparisons of thymic and extrathymic T cell development indicate that these processes involve some distinct signaling and selection events. We used mice deficient in Lck, Fyn, or both Lck and Fyn to analyze the role that these src-family PTK play in IEL development. In contrast to thymocyte development, we found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 75 publications
2
20
0
Order By: Relevance
“…43 In addition, putative IEL precursors have been reported to express low levels of B220. 44,45 The similarity between this phenotype and that expressed in the population described here raises the possibility of a lineage relationship between these subsets. However, further investigations are required to formally assess this possibility.…”
Section: Discussionmentioning
confidence: 56%
“…43 In addition, putative IEL precursors have been reported to express low levels of B220. 44,45 The similarity between this phenotype and that expressed in the population described here raises the possibility of a lineage relationship between these subsets. However, further investigations are required to formally assess this possibility.…”
Section: Discussionmentioning
confidence: 56%
“…Remarkably, these TCR Ϫ IEL did not appear to contain the CD8␣␣ ϩ subset. Thus, the absence of TCR Ϫ CD8␣␣ ϩ IEL in athymic CR␥ Ϫ/Y mice contrasts sharply with the phenotype of putative TCR Ϫ IEL precursors present in young wild-type (WT) (19), athymic (nu/nu) nude (9), SCID (9,33), RAG-1 Ϫ/Ϫ (23,24), lck Ϫ/Ϫ ϫ fyn Ϫ/Ϫ (23), CD3 Ϫ/Ϫ (24), and CD3⑀ Ϫ/Ϫ (24) mice, a predominant fraction of which expresses the CD8␣␣ homodimer.…”
Section: N Umerous Intraepithelial T Cells (Iel)mentioning
confidence: 98%
“…Accumulating evidence indicates that these CD8␣␣ ϩ IEL are potentially capable of developing somewhere in the intestinal mucosa without passing through the thymus (9,(15)(16)(17)(18)(19)(20). Moreover, the presence of lymphoid cells with properties of precursor T cells among IEL (1,9,19,(21)(22)(23)(24) and the expressions of recombination activating gene-1 (RAG-1) (9,19,21) and RAG-2 (25) by a subset of IEL support the notion that T lineage-committed precursors may enter the epithelium and undergo all steps of TCR gene rearrangement and subsequent differentiation into mature IEL in situ.…”
Section: N Umerous Intraepithelial T Cells (Iel)mentioning
confidence: 99%
“…The present study revealed that Syk-dependent γδTCR signals are indispensable for the thymic maturation and acquisition of the effector function of γδT cells. It has been demonstrated that the TCR signaling machinery differs between αβT and γδT cells (17)(18)(19)(20)(21)(22)(23)40), although these 2 cell types derive from common progenitors in the thymus. We showed here that in ex vivo γδT cells, engagement of the γδTCR-CD3 complex leads to the phosphorylation of Syk and Zap70.…”
Section: Pik3cdmentioning
confidence: 99%
“…αβT and γδT cells also show differential requirements of the Src family kinases in their development. In Lck/ Fyn-doubly deficient mice, αβT cell development is completely inhibited, whereas γδT cell development is partially impaired (21,22). Moreover, γδT cells require Blk, an Src family kinase primarily expressed in B cells, for the induction of the γδT17 subset (23).…”
Section: Introductionmentioning
confidence: 99%